Analisis Komponen Utama (PCA) Untuk Mereduksi Faktor Organisasi Pembelajaran pada Institusi Pemerintahan - Nurul Sitio; Farisadri Fauzan (Sains Manajemen: Jurnal Manajemen Unsera, 2020)
Indonesia is the most populated country in Southeast Asia. The growth population which keeps growing brings about a rapid-growing workforce every year. The limited work opportunity is unable to absorb the workforce in Indonesia. The government, in this case BP3TKI, takes a role to formulate a strategic policy regarding a conducive and qualified employment and transmigration. Some changes in the internal environment of the government affects changes from individuals in the organization. All individuals involved in it have to change, learn, and grow faster than in the past. The ability of organization and individual in responding changes will be support to face a challenge in achieving the target to create the atmosphere of employment that absorbs workforce in Indonesia. This study aims at discovering the most factor of learning organization government institution. Using PCA analysis technique, the result of this study will suggest BP3TKI of West Java in its effort to increase the learning of its employees. Keywords—learning organization